2015
DOI: 10.1007/s00167-015-3799-x
|View full text |Cite
|
Sign up to set email alerts
|

Procedural intervention for arthrofibrosis after ACL reconstruction: trends over two decades

Abstract: Purpose Arthrofibrosis is a rare complication after anterior cruciate ligament (ACL) reconstruction. The purpose of this study was to (1) report a population‐based incidence of arthrofibrosis (as defined by manipulation under anaesthesia or surgical lysis of adhesions) following ACL injury and reconstruction, (2) identify risk factors associated with development of arthrofibrosis, and (3) report outcomes of intervention for arthrofibrosis. Methods This was a historical cohort study performed in Olmsted County,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 20 publications
8
80
1
2
Order By: Relevance
“…As of June 2016 (Pubmed search) we did not find a prospective study assessing the MRI prevalence of cyclops lesions in asymptomatic patients who underwent arthroscopic ACL reconstruction. Sanders et al [22] enrolled 1841 patients retrospectively and reviewed their medical records, in particular the knee range of motion. They found that in 2% of the patients a second surgery was needed in order to treat cyclops lesions, however, the prevalence of cyclops lesions in patients without severe loss of knee extension was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of June 2016 (Pubmed search) we did not find a prospective study assessing the MRI prevalence of cyclops lesions in asymptomatic patients who underwent arthroscopic ACL reconstruction. Sanders et al [22] enrolled 1841 patients retrospectively and reviewed their medical records, in particular the knee range of motion. They found that in 2% of the patients a second surgery was needed in order to treat cyclops lesions, however, the prevalence of cyclops lesions in patients without severe loss of knee extension was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic studies have estimated the prevalence of symptomatic cyclops lesions after ACL surgery ranging between 1% and 9.8% [16, 17]. Symptomatic cyclops lesions, also referred as cyclops syndrome [8, 18], are treated by arthroscopic removal with eventually an additional notchplasty, regaining the full extension of the knee [1922]. …”
Section: Introductionmentioning
confidence: 99%
“…Fibrosis often develops after joint trauma or major surgical procedures such as total knee arthroplasty (TKA) and anterior cruciate ligament (ACL) reconstruction . Approximately, 3–10% of TKA patients are treated for arthrofibrosis, while 2–35% of ACL reconstruction patients and 14.5% of patients with knee intra‐articular fractures require intervention . The standard‐of‐care is limited to arthroscopic debridement, capsule‐release, and manipulating limbs under anesthesia.…”
mentioning
confidence: 99%
“…Failure to address knee mobility deficits can result in arthrofibrosis. Arthrofibrosis is a rare complication following ACL reconstruction that affects ~2% of patients, but does seem to respond to appropriate interventions [13]. Therefore, it is important Physical therapists limit the effects of immobilization and create a comprehensive plan of care to prevent these complications.…”
Section: Introductionmentioning
confidence: 99%